Yoga in the workplace and health outcomes: a systematic review. (18th March 2019) - Puerto Valencia, L M; Weber, A; Spegel, H; Bögle, R; Selmani, A; Heinze, S; Herr, C
Abstract: Background: Health promotion in the workplace is intended to enhance employee health and well-being. Yoga programmes are easy to implement and have been effective in the management of various health conditions. Aims: To assess the evidence regarding the effectiveness of yoga programmes at work. Methods: A search of electronic databases of published studies up until the 1st of April 2017. Inclusion criteria for the systematic review were randomized controlled trials of adult employees and yoga in the workplace. Quality appraisal was carried out using the Cochrane Collaboration's tool for assessing risk of bias in randomized trials. Results: Of 1343 papers identified, 13 studies met the inclusion criteria. Nine out of 13 trials were classified as having an unclear risk of bias. The overall effects of yoga on mental health outcomes were beneficial, mainly on stress. Most of the cardiovascular endpoints showed no differences between yoga and controls. Other outcomes reported positive effects of yoga or no change. Conclusions: The findings of this study suggest that yoga has a positive effect on health in the workplace, particularly in reducing stress, and no negative effects were reported in any of the randomized controlled trials. Further larger studies are required to confirm this.